What's wrong with the British constitution? - McLean, Ian. (Oxford : Oxford University Press, 2010)
This is a bravura critique of the traditional interpretation of the British constitution. The book demolishes many of the myths surrounding it, but also goes on to suggest a constructive alternative.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Constitutional history -- Great Britain; Constitutional law -- Great Britain -- History